Cellular structure and related physico-chemical changes during ripening of Musa AAA 'Berangan' - Ding, Phebe (Universiti Putra Malaysia Press, 2008)
Ripening is the result of complex changes and it turns an unpalatable fruit to be palatable. The distinct changes in eating quality of ripening fruits are determined by changes in their cellular structure and composition. This work was carried out to relate structural changes of Musa AAA 'Berangan' with related physico-chemical quality characteristics during ripening. The cell structure of Berangan banana was examined using scanning electron microscopy while pulp firmness, soluble solids concentration and starch pattern were determined as fruit ripened from mature green stage (ripening stage 1) until full yellow (ripening stage 6) at 27°C. As ripening progressed, the cellular structure of Berangan banana showed dramatic changes and coincided with changes in the physicochemical characteristics. The epicuticular wax and stomatal complex of peel degenerated while cell wall integrity was lost as fruit ripened. The starch began to degrade from the central core outward and concomitant with a decrease in starch granules sizes and increase of soluble solids concentration as ripening took place. The loss of cell wall integrity and conversion of starch into sugars as ripening progressed contributed to fruit softening. It is concluded that as ripening progressed, the increase in soluble solids concentration and decrease in firmness of Berangan banana fruit was closely related to the changes in the cellular structure. Keywords: Epicuticular wax, firmness, soluble solids concentration, starch granules, starch distribution pattern